Analisis Variabel Yang Mempengaruhi Earning Per Share (EPS) Pada Industri Food and Beverage Di Indonesia Tahun 2013-2017 - Erni Alfisah; Kurniaty Kurniaty (At-Tadbir : jurnal ilmiah manajemen, 2021)
The purpose of this study was to examine and analyze the effect of Current Ratio (CR), Debt to Equity Ratio (DER), Return on Equity ((ROE), and Net Profit Margin (NPM) on Earning Per Share (EPS) either partially or simultaneously. The research object used is the food and beverage industry which is listed on the IDX from 2013 to 2017. The type of research carried out is descriptive quantitative. The sample obtained after being carried out with a purposive sampling approach is 14 companies. The data used is secondary data in the form of reports financial industry food and beverage for the observation period. In this study, there are four variables, namely ROE, CR, DER, NPM as the independent variable and EPS as the dependent variable. The analysis techniques used are econometric analysis or classical assumption test, multiple regression, test of the coefficient of determination, and simultaneous test The results showed that the variables DER (X2) and ROE (X3) are partially significant significant effect on EPS (Y1), while the variables CR (X1) and NPM (X4) do not have a significant effect on EPS (Y1) and simultaneously CR, DER, ROE, and NPM have a significant effect on EPS.Keywords: Current Ratio, Debt to Equity Ratio, Return on Equity, Net Profit Margin, Earning per share